Atualidade da educação de jovens e adultos : concepção de professores-pesquisadores do centro de educação da Universidade Federal da Paraíba - Silva, Isabella Hellen Estevão da (2023)
The research addresses the challenges and possibilities of Youth and Adult Education (YAE) in contemporaneity. The reflections made in this investigation relate to the social and political field and the transformations suffered in Brazil in the last seven years (2016-2022), specifically those that affects the constitutional right responsible for guaranteeing access and permanence in education for all citizens, including those who did not finish basic education phase at the “certain age”. In this sense, the main goal of this research is to analyze the challenges and possibilities of YAE from the perspective of professors-researchers at the Education Center of Federal University of Paraíba. The following authors contributed to support the analysis proposed in the dissertation: Freire (2021; 2015; 1990; 1967), Arroyo (2005; 2011), Haddad (2000), Haddad and Di Pierro (2015) and Andrade (2021). Regarding the methodology aspect, the investigation is based on qualitative research of exploratory character, making use of a semi-structured interview carried out with four professors-researchers from Federal University of Paraíba who have Youth and Adult Education (YAE) as central object of their studies, research and/or projects. The empirical collected data was analyzed by content analysis technique, proposed by Bardin (2016). As a result of this research, the data showed that the rise of the extreme right and the implementation of neoliberal policies in Brazil in the last years contributed to the dismantling of public and social policies, weakened the public and universal sense of educational provision for the poorest and most vulnerable, as well as how, it strengthened the process of invisibilization of Youth and Adult Education (YAE) that was amplified during the pandemic period and revealed historical weaknesses still present today, such as the lack of funding and the precariousness of specific teacher training for the public of this modality. We found that these and other factors directly contribute to the decline in the number of school enrollments in Youth and Adult Education (YAE) and, consequently, the maintenance of social inequality. In conclusion, the research highlights the need to present Youth and Adult Education (YAE) as an area of knowledge within the Universities of the country, as well as the need to think about effective public and curricular policies that consider the necessity of the target audience of YAE.